PENGARUH ORIENTASI KEWIRAUSAHAAN DAN KEUNGGULAN BERSAING TERHADAP KINERJA USAHA MIKRO KECIL DI KOTA PADANG - Mentari Ritonga; Yulhendri Yulhendri (Universitas Negeri Padang, 2019)
This study aims to reveal how entrepreneurship orientation and competitive advantage affect the performance of micro and small enterprises of food and beverage in Padang City. The type of this research is descriptive and associative research. In this study, the research populations are 694 entrepreneurs of micro and small enterprises of food and beverage in Padang City. The Two Stage Cluster Random Sampling technique is used to determine the sample and the result obtained are 54 people in total. The technique of collecting data is by using questionnaires which are tested first by testing the validity and reliability before being distributed. Data analysis technique used in this study is Path Analysis. The results of this study indicate that entrepreneurship orientation significantly affects competitive advantage, entrepreneurship orientation significantly affects performance of micro and small enterprises, and competitive advantage significantly affects performance of micro and small enterprises.Keywords: Entrepreneurship Orientation, Competitive Advantage, Micro and Small Enterprises Performance